Effects of family relationships on adolescents self-control and self-efficacy - Arshat, Zarinah; Ismail, Nafesa (Invention Journals, 2017)
The purpose of this study is to determine effects of family relationships on adolescents self-control and self-efficacy. A total of 318 adolescents residing in Johor, Malaysia were involved in this study. The results revealed that family communication has significant relationship with self-control while family cohesion is associated with self-efficacy of adolescents. The study concludes that family relationships play an important role in adolescents personal competences. Further research is necessary to investigate whether these relationships are upheld over time with extended the populations to other regions.